Images of the native land in the musical and song culture of the Tuvans - Sanchai, Choigan Kh. (The New Research of Tuva, 2023)
The article presents the findings of an analysis of the image of the native land in the musical and song culture of the Tuvans and its changes in different historical periods (from the early 20th century to the present day). The scholar considers the images of the native land (‘торээн чер’ / ‘toreen cher’) in folk songs, songwriters’ songs based on folk motifs, Tuvan Soviet and post-Soviet songs. The sources comprised lyrics of songs in Tuvan from collections of different years, as well as specific songs, including two anthems of the Republic of Tuva: “Tooruktug dolgai tañdym” (“The Taiga Filled with Pine Nuts”) (1993–2011) and “Men, Tyva men” (“I am a Tuvan”) (from 2011 to the present). In folk songs, the images of home ground are concretized and emotionally tinged. These are places where people live, which are imagined as breadwinners, guardians and keepers. People are openhearted to their native places and share feelings with them. They admire these lands, complain and share sorrow with them, and nature sympathizes with humans. In songwriters’ songs that are based on folk motifs and have been written since the 1930s, we can see the broadening of the singers’ outlook — from the local area to the whole of Tuva, as well as the appearance of a collective subject — “we”. In Soviet Tuvan songs, there are almost no lyrical singers who have a reverential attitude to their native lands. The latter are viewed as nature which people must conquer and subject to their will in order to become happy and successful. They call the Soviet Union their homeland (‘торээн чурт’ / ‘toreen churt’). In Tuvan songs of the post-Soviet period, native places (‘торээн чер’ / ‘toreen cher’) are considered as lands within the borders of Tuva again and praised lyrically. Contemporary songwriters emphasize the ethnicity and ethnic identity of the Tuvans. These songs do not contain the image of a huge country, motifs of conquest, etc. But there are themes of unity, the kin relations between people and the earth again. This was also reflected in the main song of Tuva — its national anthem.